(3GdEYdGe GdEdcJQhfj (B/s - (3Tajb, MSfjfs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2005)
(3GdhXGFa GdEYdGejI ddCfJQfJ(B- (3GdUMGaI GdEdcJQhfjI(B- (3GdQGOjh YHQ GdCfJQfJ(B- (3GdJdaRjhf GdJaGYdj(B- (3GdEYdGf YHQ GdCfJQfJ(B- (3GdYdGbGJ GdYGeI YHQ GdGfJQfJ(B- (3GdOYGjI YHQ GdCfJQfJ(B- (3GfYcGSGJ GdCfJQfJ Ydi GdhSjW GdEYdGej(B.s
(3GdeQGLY U(B.233s
Keywords: (3GdEYdGe (B- (3GdEYdGf s; (3GdEYdGe GdEdcJQhfjs